Response analyses of a two-phase cryogenic tank to longitudinal and lateral accelerations. (12th October 2010) - Miralbes, R.; Castejon, L.; Carrera, M.; Valladares, D.
The aim of this article is to present a methodology for calculating vehicle tankers by analysing the way baffle shape contributes to the movement of the fluid. This methodology could be used to optimise the geometry of these parts analysing different geometries. Four different lateral types of baffles used by different cryogenic tank manufacturers have been examined. Both the movement of the fluid and the forces transmitted by the latter to the tank during emergency braking manoeuvres are analysed and the principal conclusion is that the contribution of the geometry is very important. Besides, a longitudinal baffle meant to reduce the tendency of the tank to overturn while diminishing the moment generated by the load has been designed. The longitudinal baffle has been optimised, modifying the height and depending on the level of filling of the tanker the rollover moment can be reduced.